Mesospheric winds from 70 to 98 km altitude over low latitude station Kolhapur by a partial reflection radar - Patil, P.T.; Gurubaran, S.; Rajaram, R.; Sharma, A.K.; Bhonsle, R.V. (My University, 2007)
Temporal variations of daily winds in the altitude region 70 -- 98 km from the data collected during June 2000 to April 2003 using partial reflection radar at Kolhapur (16.40°N, 74.15°E), India, are presented in this study. Sequential wind profiles are obtained using partial reflections. The horizontal component of mesospheric mean winds and their monthly variations are presented in detail. The motions implied by mesospheric drifts closely resemble movements of the neutral air. Detailed study of the seasonal variations of the zonal and meridional winds is presented.
Keywords: Wind profiles; Radio aeronomy; Data analysis; Radar; Kolhapur